Pengaruh NPF, FDR, Bank Size Dan Covid-19 Terhadap Pembiayaan UMKM Bank Umum Syariah Indonesia Periode 2018-2021 - Putri, Fitri Anisa Nusa; Mustofa, Muhammad Wakhid (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2023)
MSME has a massive contribution for the national economic development. In order to expanse and strengthening of the MSME sector, Islamic Commercial Banks as a financial intermediary should consider some of main factors before distribute its financing to MSME sector. This study aims to identify and analyze the effect of NPF, FDR, Bank Size and Covid-19 on MSME Financing at Shariah Rural Banks in Indonesia in the priode of 2018-2021 both partially and simultaneously. This study uses a panel data approach where the data needed in this study are from 7 Indonesia Islamic Banks with 112 of total data. The results of this study indicates that FDR and Bank Size variables has a positive significant effect on MSMEs Financing at Shariah Rural Banks. Meanwhile, NPF and the dummy variable Covid-19 has no significant effet on MSMEs Financing at Shariah Rural Banks.